RESEIVER DESIGNING ILS OF THE EMEREGENCY UAV SEARCH - I. I. Zabenkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the methods of the construction of a digital ILS emergency UAV search is suggested. Its design engineering, which is specified on the basis of technical parameters of the digital receiver, is carried out.